An affective model for the multiagent architecture for self-organizing and emergent systems (MASOES) - Perozo, Niriaska; Aguilar, José; Terán, Oswaldo; Molina, Heidy (Rev. Téc. Fac. Ing. Univ. Zulia)
In this work an affective model is proposed for the modeled of agents through MASOES. Each agent could change its behavior dynamically, guided by its emotional state for satisfying the objectives of the system dynamically through the self-organization of its activities. This affective model allows to MASOES to reach a commitment between the individual and collective behavior in the multiagent systems. Besides, it is possible to explain aspects of the social interaction such as the satisfaction degree, cooperation and competition, among others. This capacity to study and analyze certain social aspects is the main difference of other emotional models that normally are concentrated in the study of the relation cognition-emotion. Finally, this affective model is applied to Wikipedia in order to analyze how the emotions of each agent influence in the level of self-organization and emergence in that system.